Social attention to the scientific publications on mHealth research during Covid-19 outbreak: An altmetric study - Basumatary, Bwsrang; Gul, Sumeer; Verma, Manoj Kumar (Iberoamerican Journal of Science Measurement and Communication, 2023)
Objective. This study aimed to assess the social attention received by the top 100 highly cited scientific publications focusing on mHealth (mobile health) research during the COVID-19 outbreak. Design/Methodology/Approach. This study employed altmetric tools to assess the social attention received by mHealth research publications. The study collected bibliographical data of the top 100 highly cited articles published between 2019 and 2022 from the Scopus database. Altmetric data was collected from the Dimensions.ai database and analyzed using MS Excel, Tableau, and SPSS software. Results/Discussion. The study found that mHealth research has received significant social attention from various social media, mass media and reference manager platforms. However, it needs to be dissemination and promotion to reach wider audiences. Twitter was the leading channel for disseminating research highlights on mHealth, and articles have a significant number of readers on the Mendeley platform. However, correlation analysis revealed a weak positive correlation between citation and AAS of mHealth research publications. Conclusions. The study contributes to understanding the societal impact of mHealth research during the COVID-19 outbreak and emphasizes the role of Altmetric tools in assessing social attention in scientific publications. The study concludes by suggesting future research directions in the field.